2012
DOI: 10.1021/jp305365m
|View full text |Cite
|
Sign up to set email alerts
|

Salt Effects in the Formation of Self-Assembled Lithocholate Helical Ribbons and Tubes

Abstract: The formation of self-assembled nanotubes is usually accounted for by anisotropic elastic properties of membranelike precursors. We present experimental data as evidence of the role played by electrostatics in the formation of self-assembled tubes in alkaline aqueous suspensions of lithocholic acid (LCA). Striking salt effects are characterized by comparing the rheological, dynamical, and scattering properties of systems prepared either in stoichiometric neutralization conditions (SC) of LCA or in a large exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Terech [19], working with aggregation of lithocholate, found that increasing salt concentration led to a change from helical to cylindrical fiber morphology similar to the differences we observed in lysozyme. He ascribed the difference in fiber morphology to shielding of coulomb repulsion between like-charged structures in the fiber, resulting in a change in the conformation of the fiber helix from an open spiral to a closed tube.…”
Section: Discussionsupporting
confidence: 80%
“…Terech [19], working with aggregation of lithocholate, found that increasing salt concentration led to a change from helical to cylindrical fiber morphology similar to the differences we observed in lysozyme. He ascribed the difference in fiber morphology to shielding of coulomb repulsion between like-charged structures in the fiber, resulting in a change in the conformation of the fiber helix from an open spiral to a closed tube.…”
Section: Discussionsupporting
confidence: 80%
“…Our results are also consistent with the transition between twisted and helical shapes in self-assembled amphiphiles. 35 We also applied our theory to the shape transitions in the central hydrophobic nucleating core of the Ab peptide of Alzheimer's disease, Ab (16)(17)(18)(19)(20)(21)(22). 39,51 In solution, this peptide assembles into purely twisted ribbons or cylindrical helical ribbons.…”
mentioning
confidence: 99%
“…The various self-assembly behavior of natural BA includes the formation of tubular aggregates, provided by LCA at strong alkaline conditions (pH = 12) [171,172]. It was shown by Fang and coworkers that pH variation can induce a switch of the tubules from spiral to a straight shape by changing pH [173].…”
Section: Self-assembly Of Natural and Chemically Modified Basmentioning
confidence: 99%